« Explorer le champ des voix » - Floriane Chouraqui; Maylis Aste (EchoGéo)
At the crossroads between cinematographic studies (MA) and geography (FC), this article sets out to explore the sounds of the Cha das Caldeiras territory, in Cape Verde. It will do so through filmic experimentations led by Floriane Chouraqui. By highlighting the - human and non human - "voices" which animate this place, the study reveals their role in expressing and forming the social and spatial relationships in the heart of a territory that is truly "lived", experienced. The aim is to underline the importance of listening and the value of a particular sensibility to the various sound expressions when focusing on geographical spaces. How do we reveal, with the movie and in the movie, the complexity of the voices that shape such a territory?